2022
DOI: 10.3138/jammi-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Testing behaviour may bias observational studies of vaccine effectiveness

Abstract: BACKGROUND: Recent observational studies suggest that vaccines may have little effect in preventing infection with the Omicron variant of severe acute respiratory syndrome coronavirus 2. However, the observed effects may be confounded by patient factors, preventive behaviours, or differences in testing behaviour. To assess potential confounding, we examined differences in testing behaviour between unvaccinated and vaccinated populations. METHODS: We recruited 1,526 Australian adults for an online randomized st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…This limitation should not affect results for the ≥65 subgroup, most of whom are retired, or comparisons between BNT162b2 and ChAdOx1. Thirdly, consistent with an Australian survey, 33 we found that unvaccinated people had tested less frequently than vaccinated people during the prevaccine rollout period when widespread testing was available (table 1) and were considerably less likely to be tested during follow-up (supplementary table S7). Fourthly, differential depletion of susceptible people in the unvaccinated groups over time may lead to attenuation of hazard ratios even when true vaccine effectiveness does not change.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 85%
See 1 more Smart Citation
“…This limitation should not affect results for the ≥65 subgroup, most of whom are retired, or comparisons between BNT162b2 and ChAdOx1. Thirdly, consistent with an Australian survey, 33 we found that unvaccinated people had tested less frequently than vaccinated people during the prevaccine rollout period when widespread testing was available (table 1) and were considerably less likely to be tested during follow-up (supplementary table S7). Fourthly, differential depletion of susceptible people in the unvaccinated groups over time may lead to attenuation of hazard ratios even when true vaccine effectiveness does not change.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 85%
“…This implementation of OpenSAFELY is hosted within the TPP environment, which is accredited to the ISO 27001 information security standard and is NHS IG Toolkit compliant. 33 Data sharing: Data management and analyses were conducted in Python version 3.8.10 and R version 4.0.2. All data were linked, stored, and analysed securely within the OpenSAFELY platform (https://opensafely.org/).…”
mentioning
confidence: 99%
“…Vaccination directly influenced the attitude of patients towards their symptoms, causing a delay in seeking care and a higher symptom severity threshold needed to seek care or get tested. On contrary, vaccinated patients in other studies had higher rates of testing compared with unvaccinated 20 38. This indicates that patients’ attitude towards risk of infection and testing may vary geographically and over time.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, previous observational vaccine effectiveness studies that do not have a prescribed similar testing schedule might be biased by the potential differential testing frequencies and behaviours among people with different vaccination status. 10 , 11 Previous vaccine effectiveness studies against omicron infections have focused mainly on various mRNA vaccine candidates, including BNT162b2 (Pfizer–BioNTech) and the mRNA-1273 (Moderna) vaccine, or adenoviral vector vaccines, such as ChAdOx1 nCoV-19 (AstraZeneca), 4 , 5 , 7 , 8 , 9 , 12 and, to our knowledge, the effectiveness of inactivated vaccine (eg CoronaVac [Sinovac]) against omicron infections has yet to be investigated. Although previous studies have reported the effectiveness of BNT162b2 among children and adolescents, 9 , 12 the comparative effectiveness of BNT162b2 and CoronaVac vaccines among different age groups remains unclear.…”
Section: Introductionmentioning
confidence: 99%